Representation of Motor Movements of Elementary School Students in the Lower Grades of Nusantara University Laboratory PGRI Kediri - Himawanto, Wasis; Kholis, Moh. Nur; Zawawi, M. Anis (CV. Nusantara Sporta, 2024)
This research investigates the motor movement abilities of elementary school students at the Nusantara University PGRI Kediri Laboratory Elementary School using t-score conversion and norm categorization into five categories. Of the 146 students studied, the results showed that the distribution of motor skills included 33% of students in the